Effect of Fluorohydroxyapatite on Biological and Physical Properties of MTA Angelus - Behnam Bolhari; Nazanin Chitsaz; Sara Nazari; Marjan Behroozibakhsh; Aidin Sooratgar; Atieh Hashemian (The Scientific World Journal)
Objectives. This study aimed to assess the effect of addition of fluorohydroxyapatite (FHI) on biological and physical properties of mineral trioxide aggregate (MTA) Angelus. Materials and Methods. In this in vitro, experimental study, nano-FHI powder was first synthesized, and the morphology and chemical structure of particles were evaluated by scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), and X-ray diffraction (XRD). Three groups were evaluated in this study: MTA Angelus, MTA modified with 10% FHA, and MTA modified with 15% FHA. After mixing, the materials were applied to ring molds (10 mm diameter, 1 mm height), and the setting time of the three groups was evaluated according to ISO6876 and ASTMC266-03 with a Gillmore needle. The pH was measured using a pH meter at 24 and 48 hours and 7 days after mixing. The cytotoxicity of the materials was assessed in freshly mixed form and after 1 and 7 days using the methyl thiazolyl tetrazolium (MTT) assay according to ISO10993-5. Data were analyzed by one-way and repeated measures ANOVA and Tukey’s test (alpha = 0.05). Results. The addition of FHA to MTA significantly decreased the initial setting time (P < 0.05) and had no significant effect on cell viability (compared with pure MTA Angelus) at 1 and 7 days. However, modified MTA groups in freshly mixed form showed significantly lower cell viability (P < 0.05). The pH remained alkaline at all time points. Conclusion. Addition of 15% FHA to MTA Angelus decreased its setting time with no adverse effect on cell viability (except for fresh form) or pH.